Preparation of some 1,3,4-oxadiazole and azetidine-2-one derivatives associated with 6-nitro-3-(substituted)-quinoline-4-ol derivatives (College of Basic Education Research Journal, 2025)
This research includes  preparation of heterocyclic compounds such as 4,3,1-oxadiazole and azetidine-2-one containing the compound 4-hydroxy-6-Nitro-Quinoline. Azetidine compounds (Z12-15) were prepared from treatment of hydrazone with chloroacetic chloride, while oxadiazole compounds were prepared from  stirring of hydrazone with concentrated sulfuric acid. Hydrazone compound was prepared from  treatment of hydrazide compound with some aromatic aldehydes. Hydrazide compound was prepared by using 4-nitroaniline as a starting material with diethyl ethoxy ethylene malonate to give after heating with diphenyl ether desired Ester compound, which is then treated with aqueous hydrazine.
Keywords: Hydrazine; Oxadiazole; Azetidine; Quinolone.